Geochemical modeling of heavy metals behavior in technogenic systems - Tatyana Vladimirovna Korneeva; Nataliya Viktorovna Yurkevich; Olga Petrovna Saeva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
Relevance. Improving the quality of forecasting pollutant migration requires understanding and reflection in models of hydrochemical processes, which determine the behavior of elements in a complex multicomponent, multiphase environment, their interaction with other components. In most cases, mine drainage is a complex mixture of substances experiencing mineral phase transitions with subsequent dissolution/sedimentation, which requires the use of numerical hydrogeochemical modeling. The aim of the research is a quantitative description of hydrogeochemical processes in interaction of neutral and slightly alkaline mine waters with a river. The methods of investigation included the analysis of water samples for general chemical (potentiometric and titrimetric methods) and elemental (ISP-AES) composition and calculation modeling of chemical forms of elements in solution and saturation indexes of mineral phases using the WATEQ4f program. The results of the study showed that, despite neutral and slightly alkaline pH values of mine drainages, heavy metals and sulfates can reach extreme values, and their mobile forms of migration can pose a real threat to aquatic ecosystems and landscapes. The main chemical forms of Zn, which is the main pollutant, are sulfate and aquatic complexes. After entering the river, zinc is mainly represented by aqua-ions and carbonate complexes. Iron at all sampling sites is represented exclusively by hydroxide complexes. Calculations of saturation indices relative to minerals have revealed that the streams are supersaturated with respect to Fe(OH)3 ferrithydrite, FeOOH goethite, BaSO4 barite, which are stable both in the mixing zone and in the river. Zinc, as the predominant pollutant, forms its own mineral phase, which in composition corresponds to willemite Zn2[SiO4].